Anti-angiogenic agent sunitinib transiently increases tumor oxygenation and suppresses cycling hypoxia - Matsumoto, Shingo (2011)
Structural and functional abnormalities in tumor blood vessels impact the delivery of oxygen and nutrients to solid tumors, resulting chronic and cycling hypoxia. While chronically hypoxic regions exhibit treatment resistance, more recently it has been shown that cycling hypoxic regions acquire pro-survival pathways. Angiogenesis inhibitors have been shown to transiently normalize the tumor vasculatures and enhance tumor response to treatments. However, the effect of anti-angiogenic therapy on cycling tumor hypoxia remains unknown. Using electron paramagnetic resonance imaging (EPRI) and magnetic resonance imaging (MRI) in tumor bearing mice, we have examined the vascular re-normalization process by longitudinally mapping tumor partial pressure of oxygen (pO2) and microvessel density during treatments with a multi-tyrosine kinase inhibitor sunitinib. Transient improvement in tumor oxygenation was visualized by EPRI 2–4 days following anti-angiogenic treatments, accompanied by a 45% decrease in microvessel density. Radiation treatment during this time period of improved oxygenation by anti-angiogenic therapy resulted in a synergistic delay in tumor growth. Additionally, dynamic oxygen imaging obtained every 3 minutes was conducted to distinguish tumor regions with chronic and cycling hypoxia. Sunitinib treatment suppressed the extent of temporal fluctuations in tumor pO2 during the vascular normalization window, resulting in the decrease of cycling tumor hypoxia. Overall, the findings suggest that longitudinal and noninvasive monitoring of tumor pO2 makes it possible to identify a window of vascular renormalization to maximize the effects of combination therapy with anti-angiogenic drugs.